Cardiac rehabilitation in rural and remote areas of North Queensland: How well are we doing?. (17th March 2022) - Field, Patricia; Franklin, Richard C.; Barker, Ruth; Ring, Ian; Leggat, Peter A
Abstract: Objective: To address access to cardiac rehabilitation (CR) for people in R&R areas, this research aimed to investigate: (1) post discharge systems and support for people returning home from hospital following treatment for heart disease (HD). (2) propose changes to improve access to CR in R&R areas of NQ. Setting: Four focus communities in R&R areas of NQ. Participants: Focus communities' health staff (resident/visiting) (57), community leaders (10) and community residents (44), discharged from hospital in past 5 years following treatment for heart disease (purposeful sampling). Design: A qualitative descriptive case study, with data collection via semi‐structured interviews. Inductive/deductive thematic analysis was used to identify primary and secondary themes. Health service audit of selected communities. Results: Health services in the focus communities included multipurpose health services, and primary health care centres staffed by resident and visiting staff that included nurses, Aboriginal and Torres Strait Islander Health Workers, medical officers, and allied health professionals. Post‐discharge health care for people with HD was predominantly clinical. Barriers to CR included low referrals to community‐based health professions by discharging hospitals; poorly defined referral pathways; lack of guidelines; inadequate understanding of holistic, multidisciplinary CR by health staff, community participants and leaders; limited centre‐based CR services; lack of awareness, or acceptance of telephone support services. Conclusion: To address barriers identified for CR in R&R areas, health care systems' revision, including development of referral pathways to local health professionals, CR guidelines and in‐service education, is required to developing a model of care that focuses on self‐management and education: Heart: Road to Health.